2015
DOI: 10.1002/pon.3958
|View full text |Cite
|
Sign up to set email alerts
|

Substance use among adolescent and young adult cancer survivors

Abstract: Objective Health-promoting behaviors are recommended to childhood cancer survivors (CCS) to reduce late effects resulting from cancer treatment. Understanding factors associated with substance use is needed, especially among Hispanic CCS who are underrepresented in previous studies. The objective of this study is to examine substance use behaviors of recently treated Hispanic and non-Hispanic CCS. Methods 193 Los Angeles County CCS who were diagnosed between 2000–2007 (54% Hispanic; mean age 19.9, SD=2.8; me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
26
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 30 publications
5
26
1
Order By: Relevance
“…Current alcohol use is reported in 35% of high school students, but only 5.6% in the present study of adolescent cancer survivors. Other studies have demonstrated similar findings when compared with age‐matched peers and siblings . National rates of alcohol use among Hispanic and NHW adolescents were similar, but smoking rates among NHW adolescents were slightly higher, similar to our findings.…”
Section: Resultssupporting
confidence: 90%
See 4 more Smart Citations
“…Current alcohol use is reported in 35% of high school students, but only 5.6% in the present study of adolescent cancer survivors. Other studies have demonstrated similar findings when compared with age‐matched peers and siblings . National rates of alcohol use among Hispanic and NHW adolescents were similar, but smoking rates among NHW adolescents were slightly higher, similar to our findings.…”
Section: Resultssupporting
confidence: 90%
“…Of the few studies examining substance use behaviors among minority CCS, only 1 included adolescent survivors. Milam and colleagues recently reported no difference in substance use behaviors among Hispanic and NHW CCS . Another study on minority young adult survivors reported similar rates of smoking among Hispanic, Black, and NHW survivors .…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations